Molecular optical imaging probes for early diagnosis of drug-induced acute kidney injury - Huang, Jiaguo (2019)
Drug-induced acute kidney injury (AKI) with a high morbidity and mortality is poorly diagnosed in hospitals and deficiently evaluated in drug discovery. Here, we report the development of molecular renal probes (MRPs) with high renal clearance efficiency for in vivo optical imaging of drug-induced AKI. MRPs specifically activate their near-infrared fluorescence or chemiluminescence signals towards the prodromal biomarkers of AKI including the superoxide anion, N-acetyl-β-D-glucosaminidase and caspase-3, enabling an example of longitudinal imaging of multiple molecular events in the kidneys of living mice. Importantly, they in situ report the sequential occurrence of oxidative stress, lysosomal damage and cellular apoptosis, which precedes clinical manifestation of AKI (decreased glomerular filtration). Such an active imaging mechanism allows MRPs to non-invasively detect the onset of cisplatin-induced AKI at least 36 h earlier than the existing imaging methods. MRPs can also act as exogenous tracers for optical urinalysis that outperforms typical clinical/preclinical assays, demonstrating their clinical promise for early diagnosis of AKI.